Isolation, characterization, and antimicrobial susceptibility pattern of Escherichia coli O157:H7 from foods of bovine origin in Mekelle, Tigray, Ethiopia - Gugsa, Getachew; Weldeselassie, Million; Tsegaye, Yisehak; Awol, Nesibu; Kumar, Ashwani; Ahmed, Meselu; Abebe, Nigus; Taddele, Habtamu; Bsrat, Abrha (Frontiers in Veterinary Science, 2022)
Escherichia coli O157:H7 is an emerging and major zoonotic foodborne pathogen. It has an increasing concern for the spread of antimicrobial-resistant strains. This study aimed to isolate and characterize Shiga toxin-producing E. coli O157:H7 from raw milk, yogurt, and meat of bovine origin and determine their antimicrobial susceptibility pattern. A cross-sectional study was conducted from December 2014-June 2015 and a total of 284 milk and meat samples were collected from different sources in Mekelle. The collected samples were analyzed for the presence of E. coli and Shiga toxin-producing E. coli O157:H7 and determination of their antimicrobial susceptibility pattern following the standard bacteriological and molecular techniques and procedures, and antimicrobial sensitivity test. Out of the total 284 samples, 70 (24.6%) were bacteriologically positive for E. coli and 14.3% were found to be Shiga toxin-producing E. coli O157:H7. 100% of E. coli isolates carried the pal gene and 41.7% eaeA gene (EHEC). Of these EHEC isolates 40% and 60% were positive for stx1 and stx2, respectively. E. coli isolates showed the highest level of susceptibility to gentamycin (91.7%) but the highest level of resistance to amoxicillin (95.8%). Of the tested isolates, 18 (75%) of E. coli showed multidrug-resistant. The current study revealed the occurrence of Shiga toxin-producing E. coli O157:H7 in foods of bovine origin in the study area. In conclusion, a nationwide phenotypic and molecular characterization, in-depth typing, and drug-resistant gene identification of E. coli O157:H7 should be undertaken